Moving Toward Universal Health Coverage: Four Decades Of Experience From The Iranian Health System - Alinia C; Davoodi Lahijan J (Dove Medical Press, 2019)
Cyrus Alinia, Jalal Davoodi Lahijan Department of Health Management and Economics, School of Public Health, Urmia University Of Medical Sciences, Urmia, IranCorrespondence: Jalal Davoodi LahijanDepartment of Health Management and Economics, School of Public Health, Urmia University of Medical Sciences, 11th kilometer of Sero road, West Azarbaijan Province, Urmia 5714783734, IranTel +989395928683Email j.davoodi2020@gmail.comAbstract: Universal health coverage (UHC) during the past decade has become the main goal of the World Health Organization. Access to health services, without suffering financial hardship for the patients, constitutes the key foundation definition of UHC and its three dimensions: population coverage, service coverage, and financial protection. Iranian health policymakers have purposefully or non-purposefully been pursued the UHC goals during the last four decades by the following macro plans: Health corps, establishing and expanding Health-Care Networks, Law of Universal Health and Social Security Insurances, Family Physician, and Health Transformation Plan. In this paper, we evaluated the situation of UHC in the Iranian health system, presented the weaknesses, strengths, and challenges faced with the health system in its implementation, and finally provided some policy recommendations to complete implementation of the policy in the country.Keywords: universal health coverage, health policy, Iranian health system, health transformation plan